Clinical Assessment of Ultrasound-Guided Local Lauromacrogol Injection Combined With Curettage and Hysteroscopy for Cesarean Scar Pregnancy - Wu, Qing; Liu, Xia; Zhu, Lin; Zhu, Yichen; Mei, Tingting; Cao, Shanshan; Shen, Yan; Ding, Jun; Lin, Tan (Frontiers in Pharmacology, 2020)
Background: To evaluate the efficacy, safeness and cost of ultrasound-guided local lauromacrogol injection(USG-LLI) combined with curettage and hysteroscopy for cesarean scar pregnancy(CSP) . Methods:This was a retrospective study included 151 CSP patients diagnosed with CSP from June 2017 to December 2019, and treated by USG-LLI (n =86)or uterine artery embolization (UAE) (n =65) combined with curettage and hysteroscopy. Clinical data and outcome were analysed. Results There were no significant differences in basic clinical characteristics in the two groups. The success rates of the two groups were similar, while the complication rates (9.30%, 44.62%) of USG-LLI group and UAE group were different significantly. The total costs demonstrated a statistical difference between the two groups, which was higher in the UAE group (P < 0.05). The non-medication cost and direct medical cost of the UAE group were higher than those in USG-LLI group (P < 0.05) . Conclusions USG-LLI combined with curettage and hysteroscopy was minimally invasive and efficient for CSP. Compared with curettage after UAE, USG-LLI resulted in lower complication rate and less expense.